Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J.; Platas, G.; Pelaez, F. (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
The following values have no corresponding Zotero field: pub-location: PUBLICATIONS DEPT, BRONX, NY 10458 USA publisher: NEW YORK BOTANICAL GARDEN
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae

Identification of an endophytic Nodulisporium sp from Quercus ilex in central Spain as the anamorph of Biscogniauxia mediterranea by rDNA sequence analysis and effect of different ecological factors on distribution of the fungus - Collado, J; Platas, G; Pelaez, F (MYCOLOGIA, 2001)
A study of fungal endophytes from aerial parts of Quercus ilex ssp. ballota was carried out on 32 specimens sampled at three forests in Central Spain. Trunk bark, fresh leaves, and healthy and decaying twigs were surveyed. A Nodulisporium sp. was frequently recorded among the isolates. Sequence analysis of the internal transcribed spacer (ITS) region of the rDNA (including the 5.8S rRNA gene) was used for the identification of this fungus. The comparison and phylogenetic analysis of the sequences from several representatives of this endophytic species and a group of xylariaceous fungi with Nodulisporium-like anamorphs revealed that the endophytic Nodulisporium sp. was conspecific with the phytopathogenic species Biscogniauxia mediterranea (equivalent to Hypoxylon mediterraneum). Significant differences were found between the isolation frequencies of the fungus, relative to the geographical origin of the samples. Also, the fungus was more frequent on samples collected in the autumn, as compared to those collected in the spring. The greatest degree of colonization was observed in twigs, while in leaves the fungus was present in significantly lower amounts. The relative frequency of this species in bark increased in the higher parts of the trunk. Tissue preference analysis revealed that this fungal species is exclusively located in bark, being absent from xylem of living twigs. The relative abundance of the fungus in decaying twigs was remarkably higher than in healthy twigs.
Keywords: Distribution patterns; fungal endophytes; Hypoxylon mediterraneum; ITS sequences; Periconiella-like; Xylariaceae